Resistance to giberela and to sprouting in triticale - Zanella, Marisa Ines; Baier, Augusto Carlos (Pesquisa Agropecuaria Brasileira, 2014)
Reaction to scab Fusarium graminearum (Schw.) and pre-harvest sprouting (PHS) were investigated under field conditions in 81 triticale lines x Triticosecale (Wittmack) and the wheat variety CNT 8, at two sowing times, in 1984. Scab was evaluated in artificially inoculated spikes during anthesis, using the formula [(10 x S + 5 x MS + R)/n)]. Each line was classified in a scale from 1 to 10 (1 = resistant) (R/n) and (10 = susceptible) (10 x S/n). Partial resistance was observed in PFT 80126-2FGS, CNT 8, PFT 80137, PFT 8163-3FGS, PFT 8229, PFT 8328, PFT 80370-R-3FGS, PFT 8216 and PFT 7893. There was reduction of scab at the later planting time. No correlation was observed between scab and weather conditions after inoculation. To evaluate PHS resistance, 100 spikes per plot at physiological, complete and late maturity were taken. Fifty spikes were submitted to germination and the other half, were air dried. Germinating power (GP) was evaluated for 400 seeds and the remaining seeds where milled to determine falling number (FN). Averaging the times PFT 765-RGE2, PFT 765-29FS, PFT 80125-R-OBS and PFT 812 showed moderate resistance. There was no correlation between scab and FN or GP, and low significance levels between scores of FN and GP.